Fixed income strategies for trading and for asset management - Jonas Tinschert; Heinz Cremers (Frankfurt School of Finance & Management, 2012)
Trading and investment strategies play an essential part in better understanding fixed income markets. Over-the-counter markets and thousands of different outstanding bonds increase the difficulties to identify adequate comparison methods. Market participants and their practices differ widely depending on intentions and are often based on non-uniform decision-making figures. This working paper deals with the differing intentions of traders, treasurers and portfolio managers within fixed-income markets. The definition and implementation of exact pricing tools is a crucial undertaking for traders. Even small changes can lead to large differences in present value calculations and therefore cause mispricings. For traders, bonds are hedged against the benchmark, swapped or hold outright in their trading book. Different spread calculations against swap or benchmark are used to calculate an accurate price level. Interpolation is an essential tool to do this. For treasurers, the asset swap spread acts as the major tool to make investment decisions and after the bonds are purchased, an asset swap hedge will protect the position against yield changes. Portfolio managers are mainly seeking for duration that fits into the portfolio and the bonds are often let outright in the investment portfolio. Hedging tools are used to protect the portfolio against losses and to log in the desired key duration. The working paper examines several key points for diverse market actors and will give an overview through the fixed income market.
Keywords: C52; G12; G13; G15; L9; 330; Svensson; Nelson / Siegel; cubic spline; yield curve; hermite interpolation; zero curve; credit curve; steepener; flattener; barbell; credit basis; bullet; asset swap spread; Z-Spread; duration; BPV; basis point value; credit risk; convexity; credit trading; carry